2019
DOI: 10.1002/1873-3468.13385
|View full text |Cite
|
Sign up to set email alerts
|

Domain structure of HelD, an interaction partner of Bacillus subtilis RNA polymerase

Abstract: The HelD is a helicase‐like protein binding to Bacillus subtilis RNA polymerase (RNAP), stimulating transcription in an ATP‐dependent manner. Here, our small angle X‐ray scattering data bring the first insights into the HelD structure: HelD is compact in shape and undergoes a conformational change upon substrate analog binding. Furthermore, the HelD domain structure is delineated, and a partial model of HelD is presented. In addition, the unique N‐terminal domain of HelD is characterized as essential for its t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 36 publications
(43 reference statements)
3
13
0
Order By: Relevance
“…The presented structure confirms our previous prediction 9 where HelD, similarly to SF1 helicases, RapA and UvrD, contains a conserved Rossmann fold 1A-2A heterodimer. 1A-1 is connected with the N-terminal domain by the NG linker (HelD/145-173), which orders only in State I.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The presented structure confirms our previous prediction 9 where HelD, similarly to SF1 helicases, RapA and UvrD, contains a conserved Rossmann fold 1A-2A heterodimer. 1A-1 is connected with the N-terminal domain by the NG linker (HelD/145-173), which orders only in State I.…”
Section: Resultssupporting
confidence: 90%
“…One of these factors is HelD 5 , a protein similar to SF1 helicases 7 that associates with the RNAP core in the model gram-positive bacterium Bacillus subtilis ( Bsu ) where it was shown to be involved in transcriptional recycling 8 . HelD binds and hydrolyzes ATP and this is accompanied by conformational changes in the protein as demonstrated by SAXS experiments 9 . The absence of HelD from Bsu cells results in prolonged lag phase during outgrowth of stationary phase cells when diluted into fresh medium; overexpression of HelD then accelerates spore formation 10 .…”
mentioning
confidence: 99%
“…Superposition with the nucleic acids from the EC show that this positively-charged patch is in a position where it could interact with the downstream dsDNA (Extended Data Fig. 8a), consistent with nucleic acid-binding data 13 . It is also possible that this patch may be important for interaction with the unstructured negatively-charged C-terminal domain of δ which acts synergistically with HelD during transcription complex recycling 12 (see accompanying paper by Pei et al).…”
Section: Held Causes Major Conformational Changes In Rnapsupporting
confidence: 83%
“…Strikingly, the structure showed that HelD, which is located on the downstream side of RNAP, has two arm domains that penetrate deep into the primary and secondary channels of RNAP (clamp arm; CA, and secondary channel arm; SCA, respectively, Fig. 2b-d), which account for the strong HelD-RNAP interaction 12,13,35 . The native RNAP-HelD preparation also contained the RNAP ε subunit 19 and showed it bound on the downstream side of RNAP in a concave space between the two α, β, and β' subunits ( Fig.…”
Section: Structure Determination Of the Transcription Elongation Complexmentioning
confidence: 99%
“…HelD is widely distributed in Gram-positive bacteria and has superficial similarity to superfamily 1 (SF1) DNA helicases such as UvrD/PcrA, and its catalytic activity is ATP-dependent 12 . Lowresolution small-angle X-ray scattering data indicate that HelD undergoes an ATP-dependent conformational change and is capable of binding to DNA 13 , suggesting that these are important properties of HelD in transcription complex recycling. SF1 helicases UvrD/PcrA bind on the upstream side of RNAP, and are able to reverse-translocate it away from a site of DNA damage 6,14 .…”
mentioning
confidence: 99%